Contralateral prophylactic mastectomy: A narrative review of the evidence and acceptability - Scheepens, Josien C.C. (Breast, 2021)
The uptake of contralateral prophylactic mastectomy (CPM) has increased steadily over the last twenty years in women of all age groups and breast cancer stages. Since contralateral breast cancer is relatively rare and the breast cancer guidelines only recommend CPM in a small subset of patients with breast cancer, the drivers of this trend are unknown. This review aims to evaluate the evidence for and acceptability of CPM, data on patient rationales for choosing CPM, and some of the factors that might impact patient preferences. Based on the evidence, future recommendations will be provided. First, data on contralateral breast cancer risk and CPM rates and trends are addressed. After that, the evidence is structured around four main patient rationales for CPM formulated as questions that patients might ask their surgeon: Will CPM reduce mortality risk? Will CPM reduce the risk of contralateral breast cancer? Can I avoid future screening with CPM? Will I have better breast symmetry after CPM? Also, three different guidelines regarding CPM will be reviewed. Studies indicate a large gap between patient preferences for radical risk reduction with CPM and the current approaches recommended by important guidelines. We suggest a strategy including shared decision-making to enhance surgeons’ communication with patients about contralateral breast cancer and treatment options, to empower patients in order to optimize the use of CPM incorporating accurate risk assessment and individual patient preferences.